2023
DOI: 10.1111/liv.15500
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for autoimmune hepatitis: Pre‐transplant does not predict the early post‐transplant outcome

Abstract: Background and Aims: Autoimmune hepatitis (AIH) is a rare indication (<5%) for liver transplantation (LT). The aim of this study was to describe the early outcome after LT for AIH. Methods:A multicenter retrospective nationwide study including all patients aged ≥16 transplanted for AIH in France was conducted. Occurrences of biliary and vascular complications, rejection, sepsis, retransplantation and death were collected during the first year after LT.Results: A total of 344 patients (78.8% of women, 17.0% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(66 reference statements)
1
1
0
Order By: Relevance
“…If the earliest rAIH was observed at 3.1 months in our cohort, the median time from LT to recurrence was 53.6 months and is consistent with existing literature, reporting times to recurrence ranging from 4 to 55 months 8,17 . Of note, rAIH has little impact on patient survival after LT 9,18 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…If the earliest rAIH was observed at 3.1 months in our cohort, the median time from LT to recurrence was 53.6 months and is consistent with existing literature, reporting times to recurrence ranging from 4 to 55 months 8,17 . Of note, rAIH has little impact on patient survival after LT 9,18 …”
Section: Discussionsupporting
confidence: 88%
“…If the earliest rAIH was observed at 3.1 months in our cohort, the median time from LT to recurrence was 53.6 months and is consistent with existing literature, reporting times to recurrence ranging from 4 to 55 months. [8,17] Of note, rAIH has little impact on patient survival after LT. [9,18] Previous reports identified several risk factors for rAIH, but the results of these studies are highly conflicting (summarized in Table 4). Prados et al [5] suggested that the presence of anti-LKM1 could be a protective factor for rAIH, whereas another study demonstrated that autoantibody titers before LT do not correlate with disease activity and prognosis.…”
Section: Discussionmentioning
confidence: 99%